Effect of Y2O3 Addition on High-Temperature Oxidation of Binderless Tungsten Carbide - Wang, Jinfang; Zuo, Dunwen; Zhu, Liu; Tu, Zhibiao; Lin, Xiao; Wu, Yinan; Li, Weiwei; Zhang, Xiaoqiong (Frontiers in Materials, 2021)
High-temperature oxidation tests were carried out on binderless tungsten carbide (WC) with different Y2O3 contents (0 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, and 4 wt.%) and on YG3 cemented carbide. Results demonstrated that the addition of Y2O3 led to a significant improvement in the high-temperature oxidation resistance of binderless tungsten carbide compared with those of YG3 cemented carbide and pure tungsten carbide. After oxidation at 800 °C for 120 min, the oxidation weight gain of binderless tungsten carbide with 1 wt.% Y2O3 was 58.54 mg·cm-2, corresponding to the reduction by 47.7% compared with YG3 cemented carbide. In the high temperature oxidation process, WC in the triangle grain boundary was first oxidized to Y2WO6 due to the high activity of Y2O3 which is present mainly in the WC grain boundaries. The transport of W4+ outward along the grain boundary and the diffusion of O2- inward along the grain boundary were hindered by Y2WO6 with the high ionic radius and thus the antioxidant capacity of binderless tungsten carbide was improved. Meanwhile, the adhesive ability of oxidation layer on the substrate was enhanced with the “pinning effect” of Y2WO6, which also led to the improvement of oxidation resistance. With the Y2O3 content increasing from 1 wt.% to 4 wt.%, the antioxidant properties of binderless tungsten carbide gradually declined, and the antioxidant performance of binderless tungsten carbide with 1 wt.% Y2O3 was found to be the best.